Transfer of Fusarium mycotoxins and 'masked' deoxynivalenol (deoxynivalenol-3-glucoside) from field barley through malt to beer - Lancova, K; Hajslova, J; Poustka, J; Krplova, A; Zachariasova, M; Dostalek, P; Sachambula, L (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2008)
The fate of five Fusarium toxins--deoxynivalenol (DON), sum of 15- and 3-acetyl-deoxynivalenol (ADONs), HT-2 toxin (HT-2) representing the main trichothecenes and zearalenone (ZON) during the malting and brewing processes--was investigated. In addition to these 'free' mycotoxins, the occurrence of deoxynivalenol-3-glucoside (DON-3-Glc) was monitored for the first time in a beer production chain (currently, only DON and ZON are regulated). Two batches of barley, naturally infected and artificially inoculated with Fusarium spp. during the time of flowering, were used as a raw material for processing experiments. A highly sensitive procedure employing high-performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) was validated for the analysis of 'free' Fusarium mycotoxins and DON-conjugate in all types of matrices. The method was also able to detect nivalenol (NIV), fusarenon-X (FUS-X) and T-2 toxin (T-2); nevertheless, none of these toxins was found in any of the samples. While steeping of barley grains (the first step in the malting process) apparently reduced Fusarium mycotoxin levels to below their quantification limits (5-10 microg kg(-1)), their successive accumulation occurred during germination. In malt, the content of monitored mycotoxins was higher compared with the original barley. The most significant increase was found for DON-3-Glc. During the brewing process, significant further increases in levels occurred. Concentrations of this 'masked' DON in final beers exceeded 'free' DON, while in malt grists this trichothecene was the most abundant, with the DON/DON-3-Glc ratio being approximately 5:1 in both sample series. When calculating mass balance, no significant changes were observed during brewing for ADONs. The content of DON and ZON slightly decreased by a maximum of 30%. Only traces of HT-2 were detected in some processing intermediates (wort after trub removal and green beer).
Keywords: trichotheceny; Mycotoxins; Food Analysis; Fusarium; kontaminace potravin; manipulace s potravinami; Trichothecenes; pivo; analýza potravin; Edible Grain; jedlá semena; Beer; Food Handling; mykotoxiny; Food Contamination